Development of AdGame : AI Driven Final Overview of Game Scenarios - Nedbálková, Jiřina (2025)
This thesis addresses the challenge of enhancing the educational value of AdGame, a business simulation used at the Prague University of Economics and Business for developing analytical and managerial competences. The project focuses on designing and implementing a functional prototype of a web application that generates an AI-driven final overview of game scenarios. A Large language model (LLM) was employed to translate quantitative data into structured narrative commentary, providing lecturers with immediate, clear, and consistent feedback material for students. The development included the creation of a data dictionary, data model, structured analytical processes, and a Streamlit-based dashboard. The prototype was validated through practical tests in the MBA programme, including a comparison between lecturer-written and AI-generated summaries. Results confirmed the feasibility and pedagogical relevance of the approach, with lecturers rating the solution highly for clarity, timeliness, and usefulness. Despite limitations, such as the reliance on private technical resources and prototype status, the solution demonstrates potential for integration into the production environment and scalability into executive education and corporate training. The research contributes to the field of learning analytics by demonstrating how artificial intelligence can enrich feedback, reduce lecturer workload, and strengthen business education.